Fitness in the Endangered Gila Topminnow - Ruby J. Sheffer; Philip W. Hedrick; W. L. Minckley; Anthony L. Velasco (Conservation Biology, 1997)
The Gila topminnow (Poeciliopsis o. occidentalis) is a small, live‐bearing, endangered fish extant in a maximum of nine locales in four separate watersheds in the United States. To determine if these populations differed in their fitness, we obtained samples from the four watersheds and examined them for four fitness correlates: survival, growth rate, fecundity, and bilateral asymmetry. Earlier research found that one population, Sharp Spring, had higher allozyme heterozygosity than the other three and had higher survival, growth rate, and fecundity and lower bilateral asymmetry than a sample from one of the other populations with no polymorphic allozyme loci, Monkey Spring. We also verified that Sharp Spring fish were polymorphic for the same allozyme loci whereas the Monkey Spring population was not. We did not, however, find positive associations of allozyme heterozygosity with the four fitness correlates for the four samples. Because the earlier study had much lower survival, it is likely that the differences resulted from differential response of the two populations to a stressful laboratory environment. Whether this unknown stress occurs in natural environments or its effect is predictive of other stresses remains unresolved. As a result, we concur with suggestions in the draft recovery plan that topminnows from nearby sources be used for reintroductions and that the Sharp Spring stock not be used outside the upper Santa Cruz River drainage.